Toward a Sense of Place Unified Conceptual Framework Based on a Narrative Review: A Way of Feeding Place-Based GIS - Ahmed Rezeg; Stéphane Roche; Emmanuel Eveno (Land)
Space and place are two of the main concepts in several fields of knowledge, such as human geography, environmental psychology, urban sociology, architecture, urban planning, and others. Space is an objective and structured concept. It is mainly a physical location characterized by measured dimensions and geographical coordinates, while place is a location that holds meaning and value for an individual or a group, created through the human experience and social interactions. Sense of place is thus a set of precepted meanings and attitudinal ties toward a place (conative, affective, and cognitive bonds). From a geospatial perspective, the subjective aspect of sense of place is difficult to depict in a cartographic projection. From this angle, Place-Based Geographic Information Systems represent a set of initiatives that attempt to combine the objectivity of spaces and the subjectivity of places in digital systems, and that integrate spatial semantic characteristics as described by places’ users. In this paper, the methodological approach is mainly based on a systematic analysis and search of the scientific literature. It is a narrative review inspired and based on a scoping review strategy following the JBI methodology and the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analysis Extension for Scoping Reviews) checklist. This bibliographic analysis is about understanding the characterization and the components of sense of place. Results take the form of a synthesis of the conceptual approaches most prominent in the literature, in addition to a conceptual model encompassing the full conceptual specificities of the sense of place concept.